Predictors of trabecular bone score in school children. Issue 2 (February 2016) - Shawwa, K.; Arabi, A.; Nabulsi, M.; Maalouf, J.; Salamoun, M.; Choucair, M.; Hans, D.; El-Hajj Fuleihan, G.
Abstract Summary Trabecular bone score (TBS) is a DXA-based tool that assesses bone texture and reflects microarchitecture. It has been shown to independently predict the risk of osteoporotic fracture in the elderly. In this study, we investigated the determinants of TBS in adolescents. Introduction TBS is a gray-level textural measurement derived from lumbar spine DXA images. It appears to be an index of bone microarchitecture that provides skeletal information additional to the standard BMD measurement and clinical risk factors. Our objectives were to characterize the relationship between TBS and both age and pubertal stages and identify other predictors in adolescents. Methods We assessed TBS by reanalyzing spine DXA scan images obtained from 170 boys and 168 girls, age range 10–17 years, gathered at study entry and at 1 year, using TBS software. The results are from post hoc analyses obtained using data gathered from a prospective randomized vitamin D trial. Predictors of TBS were assessed usingt test or Pearson's correlation and adjusted using regression analyses, as applicable. Results The mean age of the study population was 13.2 ± 2.1 years, similar between boys and girls. Age, height, weight, sun exposure, spine BMC and BMD, body BMC and BMD, and lean and fat mass are all significantly correlated with TBS at baseline (r  = 0.20–0.75, p  < 0.035). Correlations mostly noted in late-pubertal stages. However, after adjustment for BMC, age remained an independent predictor only in girls. Conclusions In univariate exploratory analyses, age and pubertal stages were determinants of TBS in adolescents. Studies to investigate predictors of TBS and to investigate its value as a prognostic tool of bone fragility in the pediatric population are needed.